Respostas

2013-11-04T18:00:33-02:00
1° Por adição :
 \left \{ {{-3x+y=14} \atop {4x-y=5}} \right.
\boxed{x=19}

-3x+y=14\\-3(19)+y=14\\-57+y=14\\y=14+57\\\boxed{y=71}

2° Substituição.

 \left \{ {{5x+3y=40} \atop {4x-2y=25}} \right.

3y=40-5x
y= \frac{40-5x}{3}

Aplicando.

4x-2y=25

4x-2( \frac{40-5x}{3} )=25

 \frac{4x}{1} - \frac{80+10x}{3} = \frac{25}{1}

 \frac{12x-80+10x=75}{\not{3}}

22x=75+80\\22x=155\\\boxed{x=155/22}

Substituindo na segunda equação :

4x-2y=25
4( \frac{155}{22} )-2y=25

 \frac{620}{22} - \frac{2y}{1}= \frac{25}{1}

 \frac{620-44y=550}{\not{22}}

620-44y=550\\-44y=550-620\\44y=-550+620\\44y=70\\\boxed{y=70/44}
1 5 1